Answer:
x=2 y=1
Step-by-step explanation:
Solve the equations by substituting y=6x-11 into -2x-3y=-7.
-2x-3(6x-11)=-7
-2x-18x+33=-7
-20x+33=-7
-20x=-7-33
-20x=-40
x=2
To find y, substitute this value into the equation and solve for y.
y=6(2)-11
y=12-11
y=1
Take all three trial result averages and add them up
Then take that number and divide by three because there was three numbers added.
That number is the average of the three trials
Answer:
Kilometers most likely for any other measurement would be to small to do so otherwise.